Effect of Cadmium (Cd) on The Structure of Gill and Epipodite of Penaeid Shrimp, Penaeus japonicus Bate (Crustacea, Decapoda) - Bambang Yulianto (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2002)
Efek toksisitas sublethal cadmium terhadap struktur insang dan epipodite dari udang Penaeus japonicus dipelajari. Setelah pemaparan selama 4 hari, kadmium merubah struktur insang dari udang, akumulasi hemocyte dalam vena dan Iamela, epithelium insang mengalami disorganisasi dan kanal hemolympha distal menjadi buntu. Struktur dari epipodite juga terganggu: cadmium menyebabkan nekrosis pada permukaan. Kerusakan struktur insang dan epipodit ini menjadi argumen penurunan kapasitas hypo- dan hyper-osmoregulasi udang ini. Kata kuncl: kadmium, struktur, Penaeus japonicus, insang, epipodite.  The effect of sublethal toxicity of cadmium on the structure of gill and epipodtte of the shrimp Penaeus japonicus was studied. After 4 days of exposure, cadmium affected the gill structure of shrimp: hemocyte accumulate in vessels/channelsand lamellas, the gill epithelium is disorganised and the distal hemolymphatic lacuna is clogged. The structure of epipodites is also altered: cadmium causes superficial necrosis. The damage of gill and epipodite structure becomes a reason on the decrease of hypo- and hyper osmoregulatory capacity in this shrimp.Keywords: cadmium, structure, Penaeus Iepontcus. gill, epipodite.